Market Power and the Incentive to Innovate: A Return to Schumpeter and Arrow - TODOROVA, Tamara (Journal of Advanced Research in Management, 2021)
Using a simple linear demand and marginal cost function, we demonstrate that both competition and monopoly have incentives to innovate since this increases their profit levels. However, our results show that perfect competition is more motivated to innovate since the increase in the profit is greater with the same cost reduction and the same innovation. We also conclude that a more drastic innovation brings greater rent to the monopolist and reduces the advantages of perfect competition over monopoly. It could be presumed that monopoly firms would be attracted to more substantive innovations rather than non-drastic ones.